Does Financial Liberalization Spur Growth? - Geert Bekaert; Campbell R. Harvey; Christian Lundblad (National Bank of Belgium, 2004)
We show that equity market liberalizations, on average, lead to a one percent increase in annual real economic growth over a five-year period. The effect is robust to alternative definitions of liberalization and does not reflect variation in the world business cycle. The effect also remains intact when liberalization is instrumented with quality of institutions-variables that explain liberalization but not growth and when a growth opportunity measure is included in the regression. Capital account liberalization has a less robust effect on growth than equity market liberalization has. Other simultaneous reforms only partially account for the effect. Finally, we examine why some countries respond to equity market liberalization differently from others.
Keywords: 330; Finanzmarktregulierung; Wirtschaftswachstum; Makroökonometrie; Welt